The Case of the Wandering Kidney. (11th December 2013) - Sobel, David W.; Jumper, Brian M.
Abstract : Nephroptosis is a controversial phenomenon well described in the literature. In this case report, we present a patient whose right kidney had "wandered" from its normal anatomic position in the retroperitoneum anteriorly and was in a fixed position anterior to the liver secondary to hydronephrosis. As opposed to the suspected mechanism of nephroptosis, we offer a hydraulic theory as to the origin of the energy required to cause this translocation. The work required to move the patient's kidney was generated by her cardiac output.